Biomechanical analysis of weightlifting - Muhammad Fakhrur-Razi, Abd Rahim (2013)
Weightlifting is a sport that requires good strength and appropriate technique to make a weightlifter success in its lift. Weightlifting contains two main technique which are snatch technique and clean-jerk technique. Both techniques have six phase and the phases are, first pull; transition from first to second pull; second pull; turnover under the barbell; catching phase; rising from squat position. This project is about the biomechanical analysis on the weightlifting and the result from the experiment will be compared with other researcher. This experiment is only for preliminary study for this thesis. The objectives for this experiment are to investigate the force exerted, observe the muscle activity and study the angle of joint on the subjects while lifting the barbell for both techniques. In force distribution and muscle activity analysis, only one subject is selected to do the comparison as all subjects shows almost same pattern of graph in the experiment. From the result of angle of joint, all the subjects is compare with each other’s and only one subject is selected for comparison with the professional athlete. From the result shown by the subject and comparison with the professional athlete, the technique shown by the subject is not much different. Analysis on weightlifting also important as it can reduce the injuries and increase the performance for the lifter.